The lack of males due to illegal trapping is causing polygyny in the globally endangered Yellow Cardinal Gubernatrix cristata - Segura, Luciano Noel (2019)
We present breeding data from the southernmost populations of the globally “Endangered” Yellow Cardinal Gubernatrix cristata in Argentina, confirming the presence of current breeding populations in the region. We monitored a family group in a nesting territory composed of one male and three females throughout the breeding season 2017–2018. We found a low nest success and productivity, probably associated with the lower contribution of the male, since it was attending three reproductive females simultaneously. We attribute this uncommon case of polygyny to the lack of males in the area caused by the high intensity of male trapping for illegal trade.